Revitalisasi Tari Konvensional dalam Pertunjukan Kesenian Sandur Manduro Menuju Pertunjukan Pariwisata - Wahyudiyanto, Wahyudiyanto; Windrowati, Trinil (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2025)
The Sandur Manduro art consists of five dance performances. Each dance requires a relatively long performance time. For audiences who value time, dance performances that take a long time can feel quite tiring. In the world of tourism that values ​​time, dance performances that take up a long time are no longer interesting to present to the audience, therefore it is necessary to condense the time aspect without reducing the quality of the performance. We, as lecturers at the Sekolah Tinggi Kesenian Wilwatikta Surabaya, held a community service activity by providing a condensation activity and at the same time socializing the dances resulting from the condensation of dances in the Sandur Manduro arts. The method used is demonstration which includes: discussion, exploration, work (delivery of material -drill-), evaluation and presentation. The results of this community service are the Ayun-ayun Dance, Klana Dance and Kuda-kudaan Dance in a compact form which received high appreciation and enthusiasm from the rural community.